Symposium 4: Knowledge construction and on-line environments - Hammond, Mick; Edwards, Catherine; Levy, Philippa (Proceedings of the International Conference on Networked Learning, 2002)
The purpose of this Symposium is to explore critically ideas concerning knowledge construction and on-line environments. Three papers are offered which raise some general issues grounded in particular contexts These papers are addressing three overarching questions: what do we mean by knowledge construction? do we have a sound foundation for believing that knowledge construction takes place in on-line environments? and, what constitutes evidence for knowledge construction? The first question leads us to review attempts to theorise about knowledge creation through on-line discussion. These accounts derive from broadly social constructivist theories of learning and often place particular emphasis on communities of practice. They have a particular relevance in a ’late modern age’ when professional knowledge is subject to rapid change and more open to contestation. A common point of reference in this Symposium is the distinction between propositional knowledge and ’practical’ knowledge or ’know-how’. We ask how far this distinction is helpful in our consideration of constructing knowledge within and about the on-line learning community. The second question leads us to explore specific examples of online learning and the judgements we have reached about their effectiveness. We recognise the value of on-line learning in giving learners opportunities to share knowledge; to provide peer support; to enable a more measured and reflective type of discourse. At the same time we are aware of the constraints of time and access in the forums we have evaluated and the reticence of some learners to take part. Our experience of evaluating on-line working leads to our third question concerning the evidence of knowledge construction. We have conventional means to evalauting on-line working, such as questionnaires surveys, learners diaries and interviews, as well as new possibilities including dialogues within on-line forums and access to on-line discussion transcripts. We have worked within broadly action research perspectives that have given rise to particular issues concerning the purposes and politics of research and the validation of findings in the experience of learners. Our research poses particular ethical problems to of accountability, confidentiality and permission. Writing about such research, there is a need to acknowledge the personal nature of knowledge and the issues that arise from the researcher’s construction of case ’narratives’. Our attempts to consider professional knowledge creation within on-line forums bring us back to considering how we ourselves create our own professional knowledge. Papers: Discourses on collaborative networked learning Catherine Edwards Construction of Professional Knowledge within an On-line Environment: the Case of Teacher On-line Forums Michael Hammond Researching Networked Learning and Teaching: a Case Study in Practitioner Knowledge Construction Philippa Levy